The Students’ Opinion on Online Learning - Sirin Suhaimah; Lestari Setyowati (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
The coronavirus outbreak has impacted all aspects of human life, including the greatest impact is on education. Therefore, the education system that is being carried out conventionally must be converted into online learning to prevent the spread of COVID-19. This article aims to describe (1) the students'  opinions regarding English subjects in online learning during the COVID-19 pandemic, (2) the students' difficulties during online learning in English subjects, (3) the students' opinions about understanding the material in English subjects during online learning. This research used a descriptive qualitative design, by using interviews to get the data. The subjects of this study were 2 female and 1 male high achiever students from the first language class in Senior High School 2 situated in the area of a small town Pasuruan, East Java, Indonesia. The research instruments used were mainly personal chats interviews with the subjects of the study. The data collection was conducted in December 2020. The results showed that (1) online learning is less effective, significant, and boring; (2) difficulties that they face are unstable network, difficulty in the delivery of material provided by the teacher, and teacher’s teaching methods; (3) most of them also had difficulty in understanding the materials provided by the teacher.